The Enrichment Conditions and Resource Potential of Marine-Continental Transitional Coal-Measure Shale Gas: A Case Study of the Permo-Carboniferous Systerm in the Huanghebei Coalfield of North China - Zhou Minglei; Yin Lusheng; Shao Yubao; Wang Huaihong; Zhang Xinbin; Wu Yue; Wang Dongdong (Global Journal of Earth Science and Engineering, 2020)
Coal-measure shale gas is considered to be an important unconventional oil and gas resource in coal measures. At the present time, coal-measure shale gas has not been well studied. However, in recent years, such potential resources have received increasing attention. In this research investigation, the coal measures of the Permo-Carboniferous Period in North China’s Huanghebei Coalfield were taken as the research object in order to evaluate the enrichment conditions and resource potential of the coal-measure shale gas. The results were as follows: 1) A variety of sedimentary environments were developed during the Late Paleozoic Era in the Huanghebei Coalfield region. Lagoon sediment had mainly developed in the Taiyuan Formation, which was conducive to the high-intensity development of shale. In addition, interdistributary bay-floodplain sediment had developed in the Shanxi Formation, which was also favorable to the development of shale; 2) The average value of the total organic carbon (TOC) in the shale of the Taiyuan and Shanxi Formations in the study area was found to be more than 2%. The main type of organic matter was Type II kerogen, followed by Type III kerogen. Furthermore, the thermal evolution degree of the organic matter was considered to be in the mature stage, which indicated a good hydrocarbon generation potential; 3) The gas bearing intervals of the shale in the Taiyuan and Shanxi Formations in the study area were mainly variegated shale, mudstone, carbonaceous shale, and silty mudstone (shale), which belong to the categories of ultra-low permeability and low porosity reservoirs; 4) The average gas content of mud shale in the Taiyuan and Shanxi Formations ranges between 0.645 and 3.34 m3/t. The shale tends to have large burial depths and well-developed caprock, which is conducive to the preservation of shale gas; 5) This study’s comprehensive analysis results showed that the mud shale in the Taiyuan and Shanxi Formations have good hydrocarbon generation potential. A favorable area was delineated in the middle of the Huanghebei Coalfield, and a NE-trending belt distribution was evident along the Pandian-Qihe-Biaobaisi. In summary, the three delineated perspective areas were determined to be the Dulangkou-Zhaoguan prospect area; Yuchengnan prospect area; and Sangzidian prospect area, respectively.